Medievistica del Novecento Recensioni e note di lettura (1951-1999) - Giovanni Tabacco Paola Guglielmotti (Reti Medievali E-Book, 2007)
Guglielmotti, Paola (ed.) A comprehensive collection spanning five decades of full-length book reviews and short synopses by Giovanni Tabacco, whose scholarly concerns were never separate from a lifelong engagement as an exacting critical reader. Inspired by wide-ranging historical interests and with a special emphasis on issues of power and culture, these essays provide a valuable commentary to the progression of Medieval Studies during the twentieth century.